2006
DOI: 10.1007/s10534-006-9035-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the siderophore pyridine-2,6-bis (thiocarboxylic acid) (PDTC) in zinc utilization by Pseudomonas putida DSM 3601

Abstract: Previous work had suggested that in addition to serving the function of a siderophore, pyridine-2,6-bis(thiocarboxylic acid) (PDTC) may also provide producing organisms with the ability to assimilate other divalent transition metals. This was tested further by examining regulation of siderophore production, expression of pdt genes, and growth in response to added zinc. In media containing 10-50 microM ZnCl2, the production of PDTC was found to be differentially repressed, as compared with the production of pyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…68 Subsequent studies revealed that the zinc-pdtc complex is recognized and transported by the outer membrane receptor and inner membrane permease of the pdtc utilization machinery; however, transport of zinc-pdtc is much less efficient than transport of the iron-pdtc complex. 69 …”
Section: Siderophores As Zincophoresmentioning
confidence: 99%
“…68 Subsequent studies revealed that the zinc-pdtc complex is recognized and transported by the outer membrane receptor and inner membrane permease of the pdtc utilization machinery; however, transport of zinc-pdtc is much less efficient than transport of the iron-pdtc complex. 69 …”
Section: Siderophores As Zincophoresmentioning
confidence: 99%
“…Stabilization of harder transition metals like nickel and iron requires bischelate formation, and despite demonstrated iron binding (199), pdtc’s role in iron uptake may rely partly on its ability to reduce iron (198, 200). Nevertheless, uptake of Fe(III)-pdtc and of Zn-pdtc (201, 202) has been the major biological focus, and whether pdtc is a true chalkophore is unclear. Cu-pdtc appears to have other unusual properties, including the ability to dechlorinate the carcinogen carbon tetrachloride (203).…”
Section: Copper-binding Siderophores and Metallophoresmentioning
confidence: 99%
“…Siderophore-mediated uptake is not known; aqueous Mn(III) is stabilized and strongly bound by known Fe(III)-siderophores (Duckworth and Sposito 2005b;Farkas and Szabo 2012;Faulkner et al 1994;Harrington et al 2012a, b;Parker et al 2004) B B is an essential element to plants and may be beneficial to bacteria and animals (Adriano 2001) B is bound by several iron siderophores and may be associated with signaling in the ocean (Harris et al 2007) W Some prokaryotic redox enzymes, most notably in thermophilic bacteria (Kletzin and Adams 1996) No metallophores have been identified; however, W binds to azotochelin and protochelin, but is not taken up by A. vinelandii (Wichard et al 2008) Zn Many diverse enzymes (Morel et al 2006) No metallophores have been identified; however, there is a possible role of pyridine-2,6-bisthiocarboxylic acid (PDTC) in uptake (Leach et al 2007) by…”
Section: Mnmentioning
confidence: 99%